2021
DOI: 10.1088/2516-1083/ac34e9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of life cycle assessment of hydrogen for road transport use

Abstract: This study conducted a systematic literature review of the technical aspects and methodological choices in life cycle assessment (LCA) studies of the use of hydrogen for road transport. More than 70 scientific papers published during 2000–2021 were reviewed, in which more than 350 case studies of the use of hydrogen in the automotive sector were found. Only some studies used hybrid LCA and energetic input–output LCA, whereas most studies addressed attributional process-based LCA. A categorization based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 91 publications
(145 reference statements)
0
8
0
Order By: Relevance
“…The initial search generated 400 articles, which included 179 articles from Scopus and 221 publications from the WOS. The selection of articles comprising the systematic review followed several stages, which were conducted according to the method used by Rinawati et al (2022), as shown in Figure 1. Firstly, the raw data were filtered, considering only papers published in journals (four publications of non-peer-reviewed journal articles were excluded).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search generated 400 articles, which included 179 articles from Scopus and 221 publications from the WOS. The selection of articles comprising the systematic review followed several stages, which were conducted according to the method used by Rinawati et al (2022), as shown in Figure 1. Firstly, the raw data were filtered, considering only papers published in journals (four publications of non-peer-reviewed journal articles were excluded).…”
Section: Methodsmentioning
confidence: 99%
“…The most important information about the methodological choices and technical aspects of the selected hydrogen-based power generation LCA studies was extracted using a modified coding scheme (Muench and Guenther, 2013;Rinawati et al, 2022), as shown in the Supplementary material. We identified a case study or scenario for each variation in technological aspects such as hydrogen production method, feedstock, primary energy source, hydrogen storage, power conversion technology, and geographical scope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the promising alternative fuels considered, hydrogen production has been subject to the most environmental analysis. For example, a recent review study of the ecological effects of using hydrogen as a fuel for road transport was able to identify 72 relevant studies featuring WtT or LCA results [184]. In that literature review, a range of GWP values for WtT studies and the reference MJ could be identified.…”
Section: Hydrogenmentioning
confidence: 99%
“…With regard to different life cycle stages, the plant construction (electrolysis, carbon capture, and methanation plant) shows lower global warming potential contributions than the contributions related to plant operation [184,185].…”
Section: C-sng/l-sngmentioning
confidence: 99%